REMOTE JOB OPPORTUNITIES IN THE IT SECTOR 2020 - Mazustērniniece, Simona; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Remote work is becoming more and more popular today. Various types of technical solutions are available to contribute remote work development. At present, remote work has become more relevant due to the limits of the Covid-19 pandemic. Some sectors are prominent leaders and often work remotely, mainly IT representatives, advertising and marketers, designers, translators and others. Working remotely, IT industry uses platforms such as Skype, Zoom, Microsof Teams, etc. for communication among colleagues. The main advantage of remote work is possibility to better plan personal and working time, while the main shortcomings are the lack of corollary in person with colleagues.